Performance analysis of an experimental smart building: Expectations and outcomes - Amin, Uzma; Hossain, M. J.; Lu, J.; Fernandez, E (Elsevier, 2017)
This paper investigates the performance of an experimental green building funded by the Australian Research Council, Australia, as a part of a Zero Carbon Australia (ZCA) buildings plan to reduce energy consumption and carbon footprints. Beyond Zero Emissions (an Australian research and education organization) draws up a ZCA building plan to avoid an average global warming of greater than 2 °C and achieve zero carbon emissions from the commercial sector in a decade. In order to implement this plan, Australian Government and other non-profit organizations offer a large number of grants, subsidies and incentives to commercial building owners for energy transition from fossil fuels to renewable sources. In this paper, energy analysis of an experimental (6-star rated) green building where a range of energy conservation measures were undertaken is presented. The objective of developing this green building is to reduce emissions and energy consumption from the built environment. The outcome obtained from the monitored data has shown some significant differences from the expected and previously estimated energy saving results. This paper focuses on some possible explanations and criticalities related to the characteristics of the chosen devices and to the strategies adopted. In addition, some coordinated measures, strategies and new technologies to mitigate the highlighted problems are recommended. Furthermore, it includes several analyses to show the effectiveness of proposed recommendations. Through this case study, building designers and operators can gain insights into built-environment projects to provide more positive development solutions for the building industry in Australia and other countries.